Komunikasi Partisipatif dalam Konteks Kewirausahaan Sosial pada Program Pertanian Padi Organik di Pandeglang - Irpan Ripa’i Sutowo; Pudji Muljono; Musa Hubeis (Institut Pertanian Bogor, 2017)
Farmers welfare needs extra attention from agricultural development stakeholders. SRI's organic rice farming program implemented by the Harapan Dhuafa (Harfa) humanitarian agency in Parigi Village, Saketi Sub-district, Pandeglang District, Banten Province has scored social change agents. The steps taken by Harfa in running the program is through participatory communication approach in the process of adoption of organic rice farming innovation SRI method. The purpose of this study was to identify the characteristics of beneficiary individuals and to analyze the relationship of individual beneficiary characteristics, the intensity of participatory communication, the perception of program benefits and the level of social entrepreneurship, so that participatory communication in the context of social entrepreneurship can be well described in the organic rice farming program SRI. Research results show participative communication in the development of organic rice farming SRI method has a positive impact for the development of social entrepreneurship in Parigi Village. Through intensive participatory communication, the farmers actively engage in dialogue, arguing to reflect the results of the training/field schools in their respective fields. The emergence of individual beneficiary character in organic rice farming in increasing income and also awareness in improving environmental quality and health by producing and consuming organic rice. Based on the analysis using chi square correlation showed that there is no real relationship between the characteristics of individual beneficiaries with the intensity of participatory communication, the perception of program benefits and the level of social entrepreneurship. That is, the characteristics of individual beneficiaries is not a benchmark in an effort to increase organic rice farming methods SRI. Factors that have major influence on the intensity of participatory communication, the perception of program benefits and the level of social entrepreneurship.